TRADISI SYAIR SURAT KAPAL DALAM PERNIKAHAN MASYARAKAT MELAYU KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Bella Faniza Surya; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: A tradition verse of the ship is a tradition carried out in the event of marriage. This tradition is a tradition that has existed since the kingdom Indragiri first. Verse of the ship is verse and poetry that in which the story about meeting mate two human until it to foster home. A tradition that kept guarded and preserved until now. The purpose of this study are 1) To know the history of tradition verse of the ship in marriage Melayu society in Rengat Districk of Indragiri Hulu Regency, 2) To kno the way the implementation of the a tradition verse of the ship in marriage Melayu society in Rengat Districk of Indragiri Hulu Regency, 3) To know the values of contained in a tradition verse of the ship in marriage Melayu society in Rengat Districk of Indragiri Hulu Regency, 4) To find out the preservation of tradition verse of the ship in marriage Melayu society in Rengat Districk of Indragiri Hulu Regency. The metodh used of is stady is qualitative metodh. Data obtained from the interview then analyzed by using the language itself. Location of this stady in Rengat district of Indragiri Hulu regency. The research time begish a week after the proposal seminar until dagree seminar. Data collection techniques used a tecniqhues of interviews, observation and documentation. The result of research show that this tradition was since the kingdom Indragiri first. Stage in the implementation of the tradition verse of the ship until when the day of the implementation of the tradition verse the ships in the event of marriage.Key Word : Tradition, Verse of the Ship, Marriage